РОЗВИТОК НАЦІОНАЛЬНИХ СИСТЕМ СПЕЦІАЛЬНОЇ ОСВІТИ В ДРУГІЙ ПОЛОВИНІ XX СТОЛІТТЯ - Малишевська, Ірина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Стаття присвячена загальним тенденціям розвитку національних систем спеціальної освіти в другій половині XX століття. У новому соціокультурному контексті другої половини ХХ століття, осново-положними характеристиками якого були економічне зростання і ліберально-демократичні зміни, пильна увага з боку різних держав і урядів приділялася проблемам освіти дітей з особливими потребами. В цей період відбувається удосконалення законодавчих основ спеціальної освіти, диференціація типів шкіл і видів навчання. Необхідно відзначити, що в ранніх ініціативах, спрямованих на забезпечення освіти для всіх, задоволення спеціальних (особливих) потреб розглядалося як символічний принцип. Статья посвящена общим тенденциям развития национальных систем специального образования во второй половине XX века. В новом социокультурном контексте второй половины ХХ века, осново-полагающими характеристиками которого были экономический рост и либерально-демократические изменения, пристальное внимание со стороны различных государств и правительств уделялось проблемам обучения детей с особыми образовательными потребностями. В этот период происходит усовершенствование законодательных основ специального образования, дифференциация типов школ и видов обучения. Необходимо отметить, что в ранних государственных инициативах, направленных на обеспечение образования для всех, удовлетворение специальных (особых) потребностей рассматривалось как символический принцип. The article is devoted to the general trends of national systems of special education in the second half of the XX century. This period is characterized by the economic growth as well as liberal and democratic changes in the society. The education of children with special needs was in the focus of attention of different countries and their governments. The attitude to his social group of people has been changed. They are treated now as full members of the society enjoying equal rights with other citizens. This period is marked by the improvement of the legal framework of special education, differentiation of types of schools and types of training. Though the idea of the early initiatives was providing education for all, meeting special needs was considered to be a symbolic principle. Giving priority to children’s needs rather than to their disorders made it possible to lay the foundations of inclusive education. It involves adapting the education system to child’s needs. Hence, the inclusive form of education for children with special educational needs was introduced. The problem of formation and development of inclusive education is currently topical in Ukraine.